Behavioral responses by Icelandic White-Beaked Dolphins (Lagenorhynchus albirostris) to playback sounds - Rasmussen, Marianne H.; Atem, Ana; Miller, Lee A. (Aquatic Mammals, 2016)
AbstractThe aim of this study was to investigate how wild white-beaked dolphins (Lagenorhynchus albirostris)respond to the playback of novel, anthropogenic sounds. We used amplitude-modulated tones and synthetic pulse-bursts. (Some authors in the literature use the term “burst pulse” meaning a burst of pulses or clicks.) The tones were 2 s in duration at frequencies of 100, 200, or 250kHz in three separate playback experiments. The pulse-bursts consisted of 10 different pre-recorded white-beaked dolphin clicks from which one was chosen randomly and repeated at a rate of 300 clicks/s for 2 s. The estimated received levels for tonal signals were from 110 to 160 dB and for pulse-bursts were 153 to 166 dB re 1 μPa (peak-to-peak). Playback of a file with no signal served as a no sound control in all experiments. The animals responded to all acoustic signals with nine different behavioral responses: (1) circling the array, (2) turning around and approaching the camera, (3)underwater tail slapping, (4)emitting bubbles, (5)turning their belly towards the set-up, (6) emitting pulse-bursts towards the loudspeaker, (7) an increase in swim speed, (8) a change in swim direction, and (9) jumping. A total of 157 playbacks were conducted, 123 of which contained sound; the rest were controls. The dolphins responded behaviorally to 90 playbacks with sound. They never responded when we projected the no sound control. The data do not allow assigning specific behavioral responses to specific acoustic stimuli. We also warn of using sounds to determine hearing thresholds of wild marine mammals since their auditory sensitivity is so acute they could possibly react to distortions of the test signal and not to the intended frequency. These results clearly show, like those of earlier studies, that sounds can induce a response and a change in the natural behavior of a marine mammal—in this case, wild white-beaked dolphins. The aim of this study was to investigate how wild white-beaked dolphins (Lagenorhynchus albirostris)respond to the ...